Performance characterization of a medium-scale liquefied petroleum gas cooking stove with a two-layer porous radiant burner. (5th October 2015) - Mishra, N.K.; Mishra, Subhash C.; Muthukumar, P.
Abstract: Performance in terms of axial and radial temperature distributions, thermal efficiency, and CO and NO x emissions of a medium-scale liquefied petroleum gas cooking stove with a two-layer porous radiant burner is reported. In the two-layer burner, SiC porous matrix acts as the combustion zone, and the preheating zone consists of an alumna matrix. With burner power in the range 5–10 kW, effects of equivalence ratio on radial and axial temperature distributions, thermal efficiency and emissions are investigated. For comparison, axial temperature distributions, thermal efficiency and emissions of CO and NO x for conventional burner working in the free-flame mode are also reported. With the porous radiant burner, radial temperature distributions are almost uniform, the maximum thermal efficiency is 28% higher, and CO and NO x emissions are significantly low. Highlights: Performance characterization of LPG cooking stove is done. Burner of the stove is composed of a two layer porous matrix. Input power of the stove ranges from 5 to 15 kW. Measured temperature distributions, thermal efficiency and CO and NO x emissions are reported. Thermal efficiency is more and emissions of CO and NO x are less than conventional LPG stove.